The effect of teaching competence of prospective teachers on microteaching for class B4 students of Arabic language education - Mahmudah, Aulia Salim; Saleh, Zeiburhanus; Maulana, Asep; Irawan, Bambang (Abjadia : International Journal of Education, 2025)
Teaching competence include the ability to prepare learning plans, implement learning, and evaluate learning outcomes. In microeducation, these competencies include systematic planning of learning, selection of appropriate methods, effective classroom management, and providing constructive feedback. Mastering educational technology is also an important aspect of supporting the application of modern learning methods. Microteaching is an educational simulator that aims to train students to apply the theory of learning in real practice.This research aims to find out the extent of the impact of educational competencies on the success of mini-education for fourth grade B students at the Department of Arabic language education, Kiai Haji Achmad Siddiq Islamic State University Jember. Using quantitative methods based on survey, observation and documentation, the results of regression analysis showed a significant impact between educational competencies and microeducation.Based on the fact that the calculated value of t (4.678) exceeds the tabular value of t (2.14479), with a significance level of 0.000, which is smaller than 0.05.It shows a statistically significant relationship. The main factor of success include the preparation of a good educational plan, mastering educational material, the use of diverse methods, effective communication skill. Students are advised to engage in intensive training, receive teacher assistance and carry out continuous training to improve efficiency. It is hoped that these results will become a reference in the development of curricula for the production of professional and competent teachers.